Artificial Intelligence - a Perspective on Applicability of Deep Learning, Computer Vision and Semantic Web technologies in Medical Informatics - Catherine Tamilarasi, F; J. Shanmugam, Dr (International Journal of Engineering and Technology, 2018)
The main purpose of this paper is to Introduce Basic concepts related to Machine Learning, explore relationship between Machine learning, Deep learning and Computer Vision, understand few Deep learning models and evaluate few frequently used Deep models for computer vision. Recently Deep learning has penetrated its presence in all fields and Medical Informatics has promising applications in future. In this paper we touch base few areas of applications of Deep learning algorithms and their usage in Computer Vision.Â